2013
DOI: 10.2166/ws.2013.056
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-chemical ageing of PES/PVP ultrafiltration membranes used in drinking water production

Abstract: In water treatment by microfiltration and ultrafiltration, a major concern is the integrity loss or failure of membrane induced by onsite operations, potentially leading to permeate water contamination. This study aims to provide a better understanding of the phenomena responsible for membrane damage by analyzing its causes and effects. The role of sodium hypochlorite exposure conditions and the impact of mechanical stress on membrane characteristics were investigated. Monitoring of hydraulic response, mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…The membrane autopsy carried out by Bégoin et al [13] with spiral-wound PES ultrafiltration membranes aged under industrial conditions revealed breakage of the PES C-S bond. A similar conclusion was drawn by Arkhangelsky et al [3] by soaking PES-based membranes in bleach solutions containing 150 ppm TFC at pH 7.2 for various times corresponding to free chlorine doses up to 100 g h / L. Several studies showed that chlorine is more aggressive towards PES / PVP membranes at 7 < pH < 9 [4,9], a pH range for which the coexistence of HClO and ClOis believed to produce a significant amount of unstable radicals [14]. Yadav et al [15] studied ageing of PES spiralwound membranes by 700 ppm TFC sodium hypochlorite solutions at pH 9 and 12.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…The membrane autopsy carried out by Bégoin et al [13] with spiral-wound PES ultrafiltration membranes aged under industrial conditions revealed breakage of the PES C-S bond. A similar conclusion was drawn by Arkhangelsky et al [3] by soaking PES-based membranes in bleach solutions containing 150 ppm TFC at pH 7.2 for various times corresponding to free chlorine doses up to 100 g h / L. Several studies showed that chlorine is more aggressive towards PES / PVP membranes at 7 < pH < 9 [4,9], a pH range for which the coexistence of HClO and ClOis believed to produce a significant amount of unstable radicals [14]. Yadav et al [15] studied ageing of PES spiralwound membranes by 700 ppm TFC sodium hypochlorite solutions at pH 9 and 12.…”
Section: Introductionsupporting
confidence: 77%
“…Polyethersulfone (PES) / Polyvinylpyrrolidone (PVP) membranes are widely used for ultrafiltration and microfiltration processes, mainly because of their stability in use and cleaning conditions [1]. PES exhibits excellent chemical and thermal resistances over a wide range of pH (from 2 to 12) [2][3][4] but is relatively hydrophobic. Hydrophilic additives such as PVP are therefore added to PES in order to obtain membranes suitable for industrial applications especially for fluids containing organic compounds such as proteins or polysaccharides [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, we aim to obtain retention as an intrinsic characteristic of pristine and aged membranes while tracking the changes in permeability. In a former work [15,16] the role of sodium hypochlorite exposure conditions, especially the solution pH, on membrane characteristics has been investigated through a series of accelerated ageing experiments. The membrane was a commercially available PES/PVP hollow fiber widely used for drinking water production, the molecular weight cut-off provided by the manufacturer being 150 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the present work was to correlate the evolution of membrane characteristics to its selectivity for model solutes. Accelerated ageing experiments were performed (as in previous works [15,16]) by soaking the membrane at ambient temperature in hypochlorite solutions at a total free chlorine concentration of 350 ppm and pH 8. The model solute selected was a polydisperse Dextran, which is classically used to determine membrane molecular weight cut-off.…”
mentioning
confidence: 99%